Komunikasi Pemasaran Amanda Parfume Di Kota Medan - Aldiano, Muhammad Rasya; Deni, Indira Fatra (CV. ITTC INDONESIA, 2025)
This research analyzes the marketing communication strategy of Amanda Perfumes in Medan City in facingcompetition in the perfume industry and digital transformation. This research uses a qualitative descriptivemethod through interviews with the owner of Amanda Perfume, namely Mr. Ahmad Maulana, observations werecarried out directly at the Amanda Perfume shop address, Jl. Marelan 9 ,Medan Marelan District, Medan, NorthSumatra and the researchers' literature study used the AIDA Marketing Communication Theory (Attention,Interest, Desire, Action). The research results show that Amanda Perfume has utilized social media Facebookand Instagram to market its products, but there are still challenges to optimize the use of consumer data andcontent quality. The application of online business principles and integrated marketing strategies based ondigital technology has proven to be important for building brands and increasing competitiveness.Recommendations include improving digital content as well as data analysis to personalize marketing. It ishoped that these findings can help local businesses develop adaptive and effective marketing strategies in thedigital era